Inferior canaliculi punctal granuloma of the lacrimal system: a case report - Nur Aqilah S,; Farizal A,; Othmaliza Othman, (Faculty of Medicine, UKM Medical Centre, 2016)
Pyogenic granuloma of the eyes usually occurs after ocular surgery or inflammation related to the eyes, itself. This lesion is commonly related to procedures associated with chalazia, strabismus, or even enucleation. However, the incidence of pyogenic granuloma that arises directly from the lower canaliculi of the nasolacrimal system is rare and not being extensively reported. We report a case of an elderly lady who presented with pyogenic granuloma post EDCR with silicone stenting for left nasolacrimal duct obstruction. She presented with persistent left eye epiphora following procedure. The unusual site for pyogenic granuloma and it occurrence after EDCR raise the possibility that the condition is related to previous procedure and the material being used.